2002
DOI: 10.1144/gsl.sp.2002.195.01.27
|View full text |Cite
|
Sign up to set email alerts
|

Planktic foraminifera, particle flux and oceanic productivity off Pakistan, NE Arabian Sea: modern analogues and application to the palaeoclimatic record

Abstract: We use the flux of bulk sediment (CaC03, biogenic opal, organic carbon, lithogenic material), and of planktic foraminifera (PF) and other shell-bearing plankton from sediment trap EPT-2 off Pakistan to (1) constrain the seasonal pattern of regional productivity and (2) search for indications of the NE monsoon winter situation that may serve as a modem analogue to better reveal the seasonal climatic signals preserved in the sedimentary record of the Arabian Sea. Our trap data show a clear seasonality of fluxes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 48 publications
2
47
0
Order By: Relevance
“…To compare the modeled and observed annual distribution of the different planktonic foraminifera species we used those datasets with a minimum collecting period of one year and at least monthly resolution. We extended the database ofZarić et al (2005,2006) by adding trap data from the northwest Pacific Xu et al, 2005), Bering Sea (Asahi and Takahashi, 2007), South China Sea (Tian et al, 2005) and Arabian Sea (Schulz et al, 2002). Table 2 summarizes locations, details and references of the sediment-trap studies used in this study.…”
Section: Comparison To Sediment-trap Datamentioning
confidence: 99%
“…To compare the modeled and observed annual distribution of the different planktonic foraminifera species we used those datasets with a minimum collecting period of one year and at least monthly resolution. We extended the database ofZarić et al (2005,2006) by adding trap data from the northwest Pacific Xu et al, 2005), Bering Sea (Asahi and Takahashi, 2007), South China Sea (Tian et al, 2005) and Arabian Sea (Schulz et al, 2002). Table 2 summarizes locations, details and references of the sediment-trap studies used in this study.…”
Section: Comparison To Sediment-trap Datamentioning
confidence: 99%
“…Tindale and Pease, 1999;Sirocko et al, 2000). Satellite, sediment trap, and surface sediment data have demonstrated that the northeast monsoon does not transport significant quantities of dust to the Arabian Sea (Sirocko and Sarnthein, 1989;Clemens, 1998;Schulz et al, 2002). However, plant wax accumulation rates at sites affected by northeast monsoon winds are lower than at sites affected by the southwest monsoon winds and roughly equal to those at sites affected by the northwesterly winds.…”
Section: Accumulation Ratesmentioning
confidence: 99%
“…The observed dominance of G. glutinata in the central Red Sea (see also Fenton, 1998) is unique, since highest G. glutinata abundances in the Red Sea are today observed only in the very south (Auras-Schudnagies et al, 1989;. G. glutinata occurs in general in productive regions (Cullen and Prell, 1984;Naidu and Malmgren, 1996;Schulz et al, 2002;Storz et al, 2009), suggesting that the cause of this increase is indeed linked to productivity, as indicated by our transfer function results, although absolute values have to be taken with care due to non-analogue conditions (Fig. 5).…”
Section: Oceanography Of Mis 5 After the Sea-level Maximummentioning
confidence: 97%
“…The increasing productivity trend continues, following the increase in G. glutinata and decrease in G. sacculifer, until chlorophyll-a values return to modern conditions in KL9 at ∼110 ka BP. Absolute values between 121-112 ka BP are not reliable due to the lack of present day faunal analogues, but the high abundance of G. glutinata indicates that productivity was higher than today and during the Holocene in the central Red Sea, as this species is often associated with elevated productivity (Cullen and Prell, 1984;Naidu and Malmgren, 1996;Schulz et al, 2002).…”
Section: Reconstruction Of Surface Productivity Using Foraminiferal Tmentioning
confidence: 99%